Experimental investigation of the condensation of R134a and R404A refrigerants in a long, water-cooled, serpentine coils - Charun, Henryk; Bohdal, Tadeusz; Czapp, Marian (International journal of heat and mass transfer, 2013)
The subject of the present analysis is the condensation of the environmentally friendly refrigerants R134a and R404A in long, serpentine pipe coils, for Lc/d>800–1000, where Lc is the total length of the coiled pipe, and d is its internal diameter. During condensation in a coiled-pipe condenser, heat exchange occurs in three regimes, i.e., the superheat removal regimes, the two-phase condensation regimes and the condensate subcooling regimes. The length L of the two-phase area significantly affects the values of the average heat transfer coefficient α and the flow resistance (Δp/L) in this area. On the basis of experimental investigations of the condensation process in a long, water-cooled serpentine coil with five pipe coils of differing dimensions, it was established that the condensation mechanism in a long coil pipe differs substantially from that in a horizontal pipe. New experimental correlations were developed to calculate the average heat transfer coefficient and flow resistance in the two-phase area. In these correlations, the dimensions of the two-phase area are characterized by the geometric index L/d. The correlations developed in this study may be useful in the design of water-cooled serpentine-coil condensers.